Levothyroxine personalized treatment: is it still a dream? - Cappelli, Carlo; Gatta, Elisa; Ippolito, Salvatore (Frontiers in Endocrinology, 2024)
Levothyroxine is a milestone in the treatment of all causes of hypothyroidism. From 19th century till today, Levothyroxine experienced a great advancement, from hypodermic injections of an extract of the thyroid gland of a sheep to novel formulations, known to circumvent malabsorption issue. However, the rate of patients on suboptimal therapy is still high. Current Guidelines are clear, daily Levothyroxine dosage should be calculated based on body weight. However, we are still far away from the possibility to administer the right dosage to the right patient, for several reasons. We retrace the history of treatment with levothyroxine, pointing out strengths and weaknesses of different formulations, with particular attention to what keeps us away from tailored therapy.In the age of digitalization, the pharmaceutical industry has been giving rising importance to Digital therapeutics, that are known to be effective in reaching target therapies. By combining current knowledge of hypothyroidism therapy with cutting-edge technology, we also hypothesized what could be the future strategies to be developed in this field.